Impact of electrochemical treatment of soil washing solution on PAH degradation efficiency and soil respirometry. (April 2016) - Mousset, Emmanuel; Huguenot, David; van Hullebusch, Eric D.; Oturan, Nihal; Guibaud, Gilles; Esposito, Giovanni; Oturan, Mehmet A.
Abstract: The remediation of a genuinely PAH-contaminated soil was performed, for the first time, through a new and complete investigation, including PAH extraction followed by advanced oxidation treatment of the washing solution and its recirculation, and an analysis of the impact of the PAH extraction on soil respirometry. The study has been performed on the remediation of genuine PAH-contaminated soil, in the following three steps: (i) PAH extraction with soil washing (SW) techniques, (ii) PAH degradation with an electro-Fenton (EF) process, and (iii) recirculation of the partially oxidized effluent for another SW cycle. The following criteria were monitored during the successive washing cycles: PAH extraction efficiency, PAH oxidation rates and yields, extracting agent recovery, soil microbial activity, and pH of soil. Two representative extracting agents were compared: hydroxypropyl-beta-cyclodextrin (HPCD) and a non-ionic surfactant, Tween ® 80. Six PAH with different numbers of rings were monitored: acenaphthene (ACE), phenanthrene (PHE), fluoranthene (FLA), pyrene (PYR), benzo(a)pyrene (BaP), and benzo(g, h, i)perylene (BghiP). Tween ® 80 showed much better PAH extraction efficiency (after several SW cycles) than HPCD, regardless of the number of washing cycles. Based on successive SW experiments, a new mathematical relation taking into account the soil/water partition coefficient (Kd*) was established, and could predict the amount of each PAH extracted by the surfactant with a good correlation with experimental results (R 2  > 0.975). More HPCD was recovered (89%) than Tween ® 80 (79%), while the monitored pollutants were completely degraded (>99%) after 4 h and 8 h, respectively. Even after being washed with partially oxidized solutions, the Tween ® 80 solutions extracted significantly more PAH than HPCD and promoted better soil microbial activity, with higher oxygen consumption rates. Moreover, neither the oxidation by-products nor the acidic media (pH approximately 3) of the partially oxidized solution inhibited the general soil microbial activity during the washing cycle. Graphical abstract: Highlights: Study of successive soil washing combined to an electro-Fenton treatment considering a recirculation. Development of a model between PAHs extraction efficiency and the number of washing cycles. Extracting agents were recovered while the PAHs were completely degraded (>99%). Tween ® 80 gave better general soil microbial activity than HPCD washing agents. No interferences of intermediates and acidic partially oxidized solution on soil respirometry.